High-throughput sgRNA testing reveals rules for Cas9 specificity and DNA repair in tomato cells - Slaman, Ellen; Lammers, Michiel; Angenent, Gerco C.; de Maagd, Ruud A. (Frontiers in Genome Editing, 2023)
CRISPR/Cas9 technology can enhance plant breeding, but yet there is relatively little data on its specificity in plants. To determine the specificity and the mutagenic spectrum of SpCas9, we designed 89 g(uide)RNAs targeting genes of the tomato MYB transcription factor family with varying predicted specificities. Plasmids encoding sgRNAs and Cas9 were introduced into tomato protoplasts, and target sites as well as 224 predicted off-target sites were screened for the occurrence of mutations using amplicon sequencing. Algorithms for the prediction of efficacy of the sgRNAs had little predictive power in this system. The analysis of mutations suggested predictable identity of single base insertions. Off-target mutations were found for 13 out of 89 sgRNAs and only occurred at positions with one or two mismatches (at 14 and 3 sites, respectively). We found that PAM-proximal mismatches do not preclude low frequency off-target mutations. Off-target mutations were not found at all 138 positions that had three or four mismatches. We compared off-target mutation frequencies obtained with plasmid encoding sgRNAs and Cas9 with those induced by ribonucleoprotein (RNP) transfections. The use of RNPs led to a significant decrease in relative off-target frequencies at 6 out of 17, no significant difference at 9, and an increase at 2 sites. Additionally, we show that off-target sequences with insertions or deletions relative to the sgRNA may be mutated, and should be considered during sgRNA design. Altogether, our data help sgRNA design by providing insight into the Cas9-induced double-strand break repair outcomes and the occurrence of off-target mutations.